Of "dictator doctors" and "subjected patients" [1988]: Tuberculosis in action. Argentina 1920-1940 - Armus, Diego (1998)
The traditional history of medicine has been a history of changes in treatments and biographies of famous doctors. Beyond its specific contributions, it is a story that has little or no dialogue with social and cultural history and seems determined, above all, to reconstruct the "inevitable progress" generated by certified medicine, to unify the past of a profession that is increasingly specialized and highlight certain ethics and moral philosophy that is intended to be distinctive and emblematic of medical practice over the years.